Exploring effects of presurgical weight loss among women with stage 0–II breast cancer: protocol for a randomised controlled feasibility trial. Issue 9 (15th September 2016) - Tsuruta, Yuko; Rogers, Laura Q; Krontiras, Helen; Grizzle, William E; Frugé, Andrew D; Oster, Robert A; Umphrey, Heidi R; Jones, Lee W; Azrad, Maria; Demark-Wahnefried, Wendy
Abstract : Introduction: Obesity is a known risk factor for postmenopausal breast cancer and is associated with poorer prognosis for premenopausal and postmenopausal patients; however, the aetiological mechanisms are unknown. Preclinical studies support weight loss via caloric restriction and increased physical activity as a possible cancer control strategy, though few clinical studies have been conducted. We undertook a feasibility trial among women recently diagnosed with stage 0–II breast cancer hypothesising that presurgical weight loss would be feasible, safe and result in favourable changes in tumour markers and circulating biomarkers. Methods and analysis: A two-arm randomised controlled trial among 40 overweight or obese women, newly diagnosed with stage 0–II breast cancer and scheduled for surgery was planned. The attention control arm received upper body progressive resistance training and diet counselling to correct deficiencies in nutrient intake; the experimental arm received the same plus counselling on caloric restriction and aerobic exercise to achieve a weight loss of 0.68–0.919 kg/week. In addition to achieving feasibility benchmarks (accruing and retaining at least 80% of participants, and observing no serious adverse effects attributable to the intervention), we will explore the potential impact of an acute state of negative energy balance on tumour proliferation rates (Ki-67), as well as other tumour markers, serum biomarkers, gene expression, microbiome profiles and other clinical outcomes (eg, quality of life). Outcomes for the 2 study arms are compared using mixed models repeated-measures analyses. Ethics and dissemination: Ethics approval was received from the University of Alabama at Birmingham Institutional Review Board (Protocol number F130325009). Study findings will be disseminated through peer-reviewed publications. Given that this is one of the first studies to investigate the impact of negative energy balance directly on tumour biology in humans, larger trials will be pursued if results are favourable. Trial registration number: NCT02224807 ; Pre-results.